Application protection in 5G cloud network using zero trust architecture - Guofeng HE (Dianxin kexue)
Based on the analysis of security requirements in the era of 5G cloud-network convergence,the basic principles of zero trust were studied,including not rely on location,untrusted traffic,and dynamic access control.The basic architecture of zero-trust was studied,combining with 5G cloud network architecture,the feasible application protection solutions include the customer-built OTT model,the use of the existing VPDN model,and the public zero-trust architecture model was proposed and compared.The application scenarios of customers in 5G cloud network were analyzed,including remote access,secure cloud,mobile office,etc.In these scenarios,the value that zero-trust architecture can bring to customers was proposed,such as application hiding and dynamic control,ensure the application safety.